Zonally asymmetric influences of the quasi-biennial oscillation on stratospheric ozone - Wang, Wuke; Hong, Jin; Shangguan, Ming; Wang, Hongyue; Jiang, Wei; Zhao, Shuyun (Atmospheric Chemistry and Physics, 2022)
The quasi-biennial oscillation (QBO), as the dominant mode in the equatorial stratosphere, modulates the dynamical circulation and the distribution of trace gases in the stratosphere. While the zonal mean QBO signals in stratospheric ozone have been relatively well documented, the zonal (longitudinal) differences in the QBO ozone signals have been less studied. Using satellite-based total column ozone (TCO) data from 1979 to 2020, zonal mean ozone data from 1984 to 2020, three-dimensional (3-D) ozone data from 2002 to 2020, and ERA5 reanalysis and model simulations from 1979 to 2020, we demonstrate that the influences of the QBO (using a QBO index at 20 hPa) on stratospheric ozone are zonally asymmetric. The global distribution of stratospheric ozone varies significantly during different QBO phases. During QBO westerly (QBOW) phases, the TCO and stratospheric ozone are anomalously high in the tropics, while in the subtropics they are anomalously low over most of the areas, especially during the winter–spring of the respective hemisphere. This confirms the results from previous studies. In the polar region, the TCO and stratospheric ozone (50–10 hPa) anomalies are seasonally dependent and zonally asymmetric. During boreal winter (December–February, DJF), positive anomalies of the TCO and stratospheric ozone are evident during QBOW over the regions from North America to the North Atlantic (120 ∘ W–30 ∘ E), while significant negative anomalies exist over other longitudes in the Arctic. In boreal autumn (September–November, SON), the TCO and stratospheric ozone are anomalously high from Greenland to Eurasia (60 ∘ W–120 ∘ E) but anomalously low in other regions over the Arctic. Weak positive TCO and stratospheric ozone anomalies exist over the South America sector (90 ∘ W–30 ∘ E) of the Antarctic, while negative anomalies of the TCO and stratospheric ozone are seen in other longitudes. The consistent features of TCO and stratospheric ozone anomalies indicate that the QBO signals in TCO are mainly determined by the ...